ANALYSIS OF THE CURRENT EMPLOYMENT STATUS OF LABOR RESOURCES BY SECTORS OF THE ECONOMY (Eureka Journal of Business, Economics & Innovation Studies, 2026)
In this article, a comprehensive analysis is conducted of the current state of employment of labor force resources across sectors of the economy in the Republic of Uzbekistan, modern trends in labor market development, and the economic effectiveness of state employment policy. The relevance of the study is explained by ongoing structural changes in the global economy, the widespread introduction of digital technologies, intensifying demographic processes, increasing labor mobility, and growing competition in the labor market, which collectively reinforce the need to ensure employment and the efficient utilization of labor resources. The study summarizes theoretical perspectives and scientific approaches in the field of labor force employment and analyzes the interrelationship between the labor market, economic growth, and population employment. In particular, the factors influencing the economic activity of labor resources, mechanisms of state regulation of the labor market, the economic and social significance of employment, human capital quality, and the impact of labor productivity on economic development are scientifically substantiated.
Keywords: Labor resources, employment, labor market, economically active population, unemployment, state employment policy, human capital, labor productivity, economic growth, urbanization, informal employment, labor migration, economic sectors, digital economy, labor market regulation.